Pharmacoeconomics of individualized therapy - Janković, Slobodan (Archives of Pharmacy, 2022)
Individualization of therapy implies adjusting the choice of drug, method of administration and dosage regimen to the needs of the patient, i.e., to its genetic characteristics, comorbidities, and concomitant therapy. Optimally, it increases the cure rate, length and quality of life, while reduces the frequency and severity of adverse drug reactions. The aim is to evaluate the relationship between the costs of antibiotic therapy individualization and financial gain it achieves. The assessment of the cost-benefit ratio can be made by applying a pharmacoeconomic model with direct costs of individualization of therapy, costs of therapy and diagnostics itself, and costs of health services as inputs, and as outcomes savings achieved by shortening hospitalization, faster healing, and avoiding drug side effects and undesirable interactions. The model uses the perspective of Republic Health Insurance Fund, and the time horizon equal to life expectancy reduced by the average age of patients with nosocomial pneumonia. The comparator of individualized therapy will be standard treatment. The cost-benefit ratio of individualized therapy is significantly more favourable than the cost-benefit ratio of standard antibiotic therapy of hospital-acquired pneumonia. Main savings are due to the reduction of mortality, shortening of hospitalization and reduction of antibiotic consumption per patient. If the hospital has clinical pharmacologists or clinical pharmacists employed, the costs of the individualization procedure are minimal, and the savings are much greater. Systematic application of individualized antibiotics use has great potential for reducing the total cost of healthcare in hospitals and creating opportunities for investment in innovative health technologies.